2016
DOI: 10.5334/labphon.38
|View full text |Cite
|
Sign up to set email alerts
|

Stress Effects on Stop Bursts in Five Languages

Abstract: This study examines the effects of stress on the stop burst in five languages differing in number of places of articulation, as reflected in burst duration, spectral centre of gravity, and spectral standard deviation. The languages studied are English (three places of articulation /p t k/), the Indonesian language Makasar (four places /p t c k/), and the Central Australian languages Pitjantjatjara, Warlpiri (both five places /p t ʈ c k/), and Arrernte (six places /p t̪ t ʈ c k/). We find that languages differ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 38 publications
(53 reference statements)
0
8
0
Order By: Relevance
“…Tabain et al (2016a) found that there was a large gap between F1 and the higher formants in the Australian laterals, which are impressionistically described as relatively "clear." Such a large gap is considered a characteristic of the lateral "ringing" sound, and the fact that the gap was between F1 and F2, rather than F2 and F3, led Tabain et al (2016a) to suggest that the primary antiresonance for the lateral is at a much lower frequency than had previously been proposed (see Tabain et al, 2016a, for further discussion of the different acoustic models). This antiresonance arises from a side branch to the main airflow (which is along the sides of the tongue for lateral consonants), with the side branch created by the pocket of air trapped along the midline behind the portion of the tongue forming the central constriction.…”
Section: Laterals In Central Australian Languagesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tabain et al (2016a) found that there was a large gap between F1 and the higher formants in the Australian laterals, which are impressionistically described as relatively "clear." Such a large gap is considered a characteristic of the lateral "ringing" sound, and the fact that the gap was between F1 and F2, rather than F2 and F3, led Tabain et al (2016a) to suggest that the primary antiresonance for the lateral is at a much lower frequency than had previously been proposed (see Tabain et al, 2016a, for further discussion of the different acoustic models). This antiresonance arises from a side branch to the main airflow (which is along the sides of the tongue for lateral consonants), with the side branch created by the pocket of air trapped along the midline behind the portion of the tongue forming the central constriction.…”
Section: Laterals In Central Australian Languagesmentioning
confidence: 99%
“…This particular range was chosen for the study of Tabain et al (2016d) study because the range below 1 kHz is dominated by voicing, and because preliminary explorations had suggested that the frequency range above 5 kHz did not add much information. However, while Tabain et al (2016a) only presented CoG and SD measures, we present all 4 of the standard spectral moments in the present study, given that we are also examining the retroflex (postalveolar) rhotic of Malayalam, and as such we wanted to give a more complete overview of the /ɭ/ vs. /ɻ/ contrast in this language.…”
Section: Labelling and Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…All vocalic and prosodic contexts were included. In particular, it should be noted that no attempt was made to separate the apicals (alveolar or retroflex) according to prosodic context: the apical contrast is in principal neutralized in wordinitial position [7,17], and the retroflex is more prototypically retroflex when it is in unstressed position [18]. Tongue spline data were sampled at the acoustic onset, midpoint, and offset of the consonant.…”
Section: The Current Studymentioning
confidence: 99%
“…a more posterior release for the retroflex as compared to the alveolar [16]). When analyzed according to prosodic context [17], there is some evidence that the spectral centre of gravity is higher for the alveolar in a strong prosodic context than in a weak prosodic context, suggesting a more forward release of the alveolar preceding a stressed vowel.…”
Section: Introductionmentioning
confidence: 99%